A line follower educational mobile robot performance robustness increase using a competition as benchmark - Gonçalves, José (2020)
In this paper it is presented a line follower educational mobile robot performance robustness increase. The Robotic Day line Follower Competition was used as a Benchmark to test the proposed approach. The applied robot is based on an Arduino, which is applied in the low level control, while the high level control loop is carried out by an RPI running an object pascal application. The described robot was prototyped in order to have a competitive participation in the Robotic Day Line Follower 2017 competition, and improved for performance robustness increase in order to participate in the 2018 competition. It was prototyped with an RPI, taking advantage of its capabilities, allowing the use of higher performance sensors, when compared with the most common standard approaches based on a single 8 bit RISC micro-controller, having as disadvantage the inevitable robot size increase, which compromises in certain situations the robot maneuverability and increases the power consumption. The robot is equipped with DC Motors, the chosen line follower sensor is the picamera and for the obstacle detection, a time of flight sensor was applied.